74.6k views
3 votes
Can somebody step by step explain how to solve this problem??

(3x^2y)(-7xy^3)

2 Answers

5 votes

Answer:

-21 · x³ · y^4

Step-by-step explanation:

Let's do this multiplication in 3 parts:

3(-7) = -21, and:

x2 · x = x³, and:

y · y³ = y^4

Multiplying these three factors together results in -21 · x³ · y^4

User Jacq
by
4.9k points
4 votes

Answer:


\boxed{\bold{-21x^3y^4}}

Step-by-step explanation:

[ Step One ] Remove Parenthesis: (a) = a


\bold{-3x^2y\cdot \:7xy^3}

[ Step Two ] Multiply:
\bold{3\cdot \:7=21}


\bold{-21x^2xy^3y}

[ Step Three ] Apply Exponent Rule
\bold{\:a^b\cdot \:a^c=a^(b+c): \ x^2x=\:x^(2+1)=\:x^3}


\bold{-21x^3y^3y}

[ Step Four ] Apply Exponent Rule:
\bold{y^3y=\:y^(1+3)=\:y^4}


\bold{-21x^3y^4}

[
\boxed{\bold{Final \ Answer}} ]


\bold{-21x^3y^4}


\boxed{\bold{Mordancy}}

User Nzinga
by
5.0k points